Proyecto de inversión para la exportación de piña de Colombia hacia el mercado de Seúl - Corea del Sur (2021)
This investment project to export unprocessed pineapple from Colombia to Seoul market - South Korea. This fruit is considered in recent years as one of the most important in the world in terms of commercial and production, for their excellent nutritional properties. South Korea as a market target, is one of the economies strong and solid in the world, since studies show that its population has a power high purchasing power and therefore the demand for this fruit has been increasing over the years. years. In order to demonstrate that this project is feasible, some studies that will help to establish if this type of project can be started or if not it is feasible to do so, these studies are: the market study, technical study, administrative, legal, economic and financial